Application of the Brillouin Optical Scanning System in the Regional Corneal Biomechanical Evaluation of Keratoconus and Its Correlation with Corvis ST Parameters - Qiuruo Jiang; Yichen Sun; Zhanhao Gu; Lumeng Wang; Yiqiang Wu; Jialu Chen; Zhiyi Chen; Xiaobo Zheng; Shihao Chen (Bioengineering, 2025)
(1) Background: The early diagnosis of keratoconus is critical for prognosis. Traditional methods like ORA and Corvis ST measure overall corneal biomechanics but lack regional specificity and are affected by intraocular pressure. In contrast, Brillouin microscopy assesses regional corneal biomechanics without such limitations; (2) Methods: In total, 25 keratoconus patients and 28 healthy controls were included in this study. Corneal biomechanics were measured using the BOSS system (Brillouin Optical Scanning System) in a 10-point mode within an 8 mm diameter, and included the mean, maximum, minimum and standard Brillouin shift. The Corvis ST parameters extracted included the CBI (Corneal Biomechanical Index), CCBI (Corvis Biomechanical Index for Chinese populations), SSI (Stress–Strain Index), DA (Deformation Amplitude), IIR (Inverse Integrated Radius), and SP-A1 (Stiffness Parameter at First Applanation); (3) Results: BOSS showed significant differences in the inferior nasal region (p = 0.004) and central region (p = 0.029) between groups, but not in peripheral regions (p = 0.781). In a comparison of the Brillouin frequency shifts measured between groups, there was no difference in the Mean (p = 0.452) and Max (p = 0.487), but the Min (p = 0.003), Standard (p = 0.000), and Max–Min (p = 0.006) all showed differences. Corvis ST identified significant differences in six parameters (CBI, CCBI, SSI, DA, IIR, and SP-A1) between groups (p < 0.001). Correlations were found between the BOSS and Corvis ST results, with moderate correlations in the inferior nasal region; (4) Conclusions: The BOSS Brillouin microscope can provide an accurate diagnostic evaluation for the corneal biomechanical differences between normal eyes and keratoconus, independent of IOP (Intraocular Pressure) and CCT (Central Corneal Thickness), with a good correlation with Corvis ST, especially in assessing regional biomechanics.